2017
DOI: 10.1016/j.heliyon.2017.e00405
|View full text |Cite
|
Sign up to set email alerts
|

Paclitaxel induces Stathmin 1 phosphorylation, microtubule stability and apoptosis in acute lymphoblastic leukemia cells

Abstract: Acute lymphoblastic leukemia (ALL) is a hematological malignancy characterized by abnormal proliferation and accumulation of lymphoblasts in the hematopoietic system. Stathmin 1 is a proliferation marker for normal lymphocytes, which has been described as highly expressed in ALL patients and functionally important for leukemia phenotype. In the present study, we expand our previous observations and aim to investigate Stathmin 1 expression and its impact on laboratory features and clinical outcomes in an indepe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 21 publications
(29 reference statements)
0
2
1
2
Order By: Relevance
“…In addition, paclitaxel enhances stathmin phosphorylation in acute lymphoblastic leukemia cells and increases PP2A expression in non-small cell lung cancer (NSCLC) cells. 33,34) However, paclitaxel had no effect on stathmin phosphorylation and PP2A expression in ovarian cancer cells in this study. These results suggest that phosphorylation of stathmin induced by microtubuleassociated drugs, including eribulin and paclitaxel, might be differently regulated in different types of cancer cells.…”
Section: Discussioncontrasting
confidence: 61%
“…In addition, paclitaxel enhances stathmin phosphorylation in acute lymphoblastic leukemia cells and increases PP2A expression in non-small cell lung cancer (NSCLC) cells. 33,34) However, paclitaxel had no effect on stathmin phosphorylation and PP2A expression in ovarian cancer cells in this study. These results suggest that phosphorylation of stathmin induced by microtubuleassociated drugs, including eribulin and paclitaxel, might be differently regulated in different types of cancer cells.…”
Section: Discussioncontrasting
confidence: 61%
“…Some studies show that chemotherapeutic agents that target microtubules affect the phosphorylation status of stathmin. Vinblastine, a microtubule destabilizer, increases stathmin phosphorylation in a non‐small cell lung cancer (NSCLC) cell line, 27 and Machado‐Neto et al 28 showed that PTX, a microtubule stabilizer, induces stathmin phosphorylation in acute lymphoblastic leukemia cells. Vinblastine reduces PP2A expression, whereas PTX increases it markedly, in NSCLC cells 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Stathmin (also known as stathmin 1, Op18, p18, p19, and metablastin) is a highly-conserved protein in various species and is essential for regulating the cell cycle [ 12 , 13 ], microtubules [ 14 , 15 ] and apoptosis [ 16 , 17 ]. Stathmin is reported to be involved in arsenic trioxide-induced apoptosis in human cervical cancer cell lines [ 15 ].…”
Section: Introductionmentioning
confidence: 99%